The Effect of Professionalism Teacher Management and Teacher Performance Motivation on Teacher Performance Results in SMAN 25 Kab. Tangerang Gugus 08 Kab. Tangerang, Banten Province - Siti Amyanih; Herry Sussanto (Dinasti Publisher, 2022)
This study aims to analyze (1) teacher management professionalism of teachers on teacher performance at Sman 25 kab. Tangerang (2) The effect of teacher performance motivation on teacher performance outcomes at Sman 25 Kab. Tangerang (3) The influence of teacher management professionalism and teacher performance motivation on results. Teacher performance at sman 25.Tangerang. This study uses a quantitative method and uses a questionnaire as a research instrument. The data were collected from ninety-four teachers from fourteen different high schools in the Cluster 08 district, Tangerang Regency. The collected data were then analyzed using simple linear regression analysis methods and linear regression analysis. multiple with quantitative approach. The results of the analysis show that (1) the variable of teacher management prefessionalism (X1) has a partial positive effect on teacher performance. This is shown by the value of the regression coefficient (X1) of 32.6% (2) The variable of teacher performance motivation (X2) has a partially positive effect on teacher performance. This is shown by the value of the regression coefficient of X2 of 46.2% and ( 3) Professionalism teacher management variables together with teacher performance motivation have a positive effect on teacher performance results. This is indicated by the regression coefficient value of 47.1%.